THE CAPACITY PROBLEMS AND CRISIS SITUATION IN ROAD TRANSPORT (Perner's Contacts, 2006)
The government or the commissioner accepts some regulation precaution in the time of crisis’s situations. Some of the regulation precautions regulate the road transportation on the public road transport. The paper deals with the regulation precautions which cut the capacity of the crossroads and the roads. The possibly regulation precautions which increase of their capacity and are possibly in crisis’s situations are written in this paper.